If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5u + 5 = -10 Reorder the terms: 5 + 5u = -10 Solving 5 + 5u = -10 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 5u = -10 + -5 Combine like terms: 5 + -5 = 0 0 + 5u = -10 + -5 5u = -10 + -5 Combine like terms: -10 + -5 = -15 5u = -15 Divide each side by '5'. u = -3 Simplifying u = -3
| 3x+5y=-67 | | 4+5m=12+3m | | 12x^3-12x^2+8=0 | | (X/15)=15 | | x+70+75+x+45=180 | | 2(x-4)=3x+32 | | 20a+13b+6c+6c-6b-4a= | | -3x-y=26 | | (y^1/8)=-1 | | 63x+9=36 | | 2t-11=15 | | -3x+3y=30 | | 15x-3=8x+16+44 | | cotg4x/cotg3x | | 8u=4v-34 | | 4x+-2y=24 | | -4x+y=-27 | | 8x=6x-10+30 | | 8x/3-8=8 | | 4h+9=33 | | 7u+5=2u-10 | | 4(x-4)+1=4x-14 | | (4/3)/(5/4) | | 10(z+4)-4(z-2)=2(z-3)+3(z-1) | | 2(4X-11)=2 | | -5x+5y=-25 | | x^2+x^2=57 | | 4=-3(24-y)+2(y-2) | | 4(x-7)+15=4x-13 | | 3x-3=-26 | | 0.09xX=69.59 | | 3y-27=-6 |